PENATAAN LAYOUT INTEGRATED FARMING KEBUN BUAH EDUWISATA BENDOSARI - Faridah, Eulis Yulianti (UIN Sunan Kalijaga, 2024)
Bendosari orchard, which has been transformed into an edu-tourim orchard, is the result of a collaboration between the orchard manager and UIN Sunan Kalijaga Yogyakarta. To complement the educational program in the orchard, integrated farming is made which aims to create an efficient and environmentally friendly agricultural system, and can provide more economic and social benefits for the local community. The creation of a layout for integrated farming in this edu-tourism orchard applies a descriptive method with a sustainable design orientation. Some key aspects of the design include site analysis, precedent study, sustainable principles implementation study, concept, and design creation. The design that will be used as a reference for this development considers aspects of space, circulation aspects, aspects of vegetation and commodities, as well as facilities that accommodate integrated farming systems and edu-tourism aspect. In this integrated farming system, fish pond areas, sheep farms (sheep pens, sheep feed areas, fertilizer making areas, feeding areas as tourist facilities) and of course the existing plantation areas are also designed. There are many advantages and benefits that can be obtained from the implementation of this system, especially when combined with educational activities. ======================================== Kebun buah Bendosari yang bertansformasi menjadi kebun eduwisata adalah hasil dari kerjasama pengelola kebun dengan UIN Sunan Kalijaga Yogyakarta. Untuk melengkapi program edukasi dalam kebun, dilakukan pembuatan integrated farming yang bertujuan untuk menciptakan sistem pertanian yang efisien dan ramah lingkungan, serta dapat memberikan manfaat ekonomi dan sosial yang lebih bagi masyarakat setempat. Pembuatan layout untuk integrated farming pada kebun buah eduwisata ini menerapkan metode deskriptif dengan berorientasi pada desain yang berkelanjutan. Beberapa aspek kunci dalam perancangan tersebut seperti analisis tapak, studi preseden, studi implementasi prinsip berkelanjutan, konsep, dan pembuatan desain. Desain yang akan digunakan sebagai acuan pembangunan ini mempertimbangkan aspek ruang, aspek sirkulasi, aspek vegetasi dan komoditasnya, serta fasilitas yang mengakomodir sistem integrated farming serta eduwisatanya. Pada sistem integrated farming ini juga didesain area kolam ikan, peternakan domba (kandang domba, area pakan domba, area pembuatan pupuk, area feeding sebagai sarana wisata) dan tentu saja area perkebunan yang memang sudah ada. Banyak keuntungan dan manfaat yang bisa didapatkan dari penerapan sistem ini, terlebih lagi jika dipadukan dengan kegiatan eduwisata.